EROSION CALDERAS: ORIGINS, PROCESSES, STRUCTURAL AND CLIMATIC CONTROL - Karátson D.; Thouret J.C.; Moriya I.; Lomoschitz A. (My University, 1999)
The origin and development of erosion-modified, erosion-transformed, and erosion-induced depressions in volcanic terrains are reviewed and systematized. A proposed classification, addressing terminology issues, considers structural, geomorphic, and climatic factors that contribute to the topographic modification of summit or flank depressions on volcanoes. Breaching of a closed crater or caldera generated by volcanic or non-volcanic processes results in an outlet valley. Under climates with up to ∼2000–2500 mm annual rainfall, craters, and calderas are commonly drained by a single outlet. The outlet valley can maintain its dominant downcutting position because it quickly enlarges its drainage basin by capturing the area of the primary depression. Multi-drained volcanic depressions can form if special factors, e.g., high-rate geological processes, such as faulting or glaciation, suppress fluvial erosion. Normal (fluvial) erosion-modified volcanic depressions the circular rim of which is derived from the original rim are termed erosion craters or erosion calderas, depending on the pre-existing depression. The resulting landform should be classed as an erosion-induced volcanic depression if the degradation of a cluster of craters produces a single-drained, irregular-shaped basin, or if flank erosion results in a quasi-closed depression. Under humid climates, craters and calderas degrade at a faster rate. Mostly at subtropical and tropical ocean-island and island-arc volcanoes, their erosion results in so-called amphitheater valleys that develop under heavy rainfall (>∼2500 mm/year), rainstorms, and high-elevation differences. Structural and lithological control, and groundwater in ocean islands, may in turn preform and guide development of high-energy valleys through rockfalls, landsliding, mudflows, and mass wasting. Given the intense erosion, amphitheater valleys are able to breach a primary depression from several directions and degrade the summit region at a high rate. Occasionally, amphitheater valleys may create summit depressions without a pre-existing crater or caldera. The resulting, negative landforms, which may drain in several directions and the primary origin of which is commonly unrecognizable, should be included in erosion-transformed volcanic depressions.